Towards a more effective delivery of the school health and nutrition program of public elementary schools in the Municipality of Binmaley, Pangasinan - Miranda, Anthony G. (University of Pangasinan : [s.n.], 2019)
This study - entitled "Towards a More Effective Delivery of the School Health and Nutrition Program of Public Elementary Schools in the Municipality of Binmaley, Pangasinan" - aimed to come up with a proposed delivery scheme to enhance the implementation of the school health and Nutrition Program (SHNP) in public elementary schools in the Municipality of Binmaley, Pangasinan. to come up with the proposed delivery scheme, the researcher determined the level or implementation of the SHNP along the components of health education, health and nutrition services, healthful school living, and school-community coordination for health and nutrition as perceived by the principals and teachers; and, the problems encountered by the schools in the implementation of the SHNP. The writer hopes that, through the policy recommendations, the implementation of the school health and nutrition program of the public elementary schools will be enhanced for the benefit not only of the pupils but the teachers, the school heads, and the school as well.
Bibliography: pages 125-130.
CHED-La Union
Keywords: Nutrition -- Education